Preventive effects of Capparis Spinose extract on experimental periodontitis in rats: a histopathological and biochemical study.: Capparis Spinose and Experimental Periodontitis - Gündoğar, Hasan; Özdemir, Hakan; Şahin İnan, Zeynep Deniz (Cellular and Molecular Biology, 2023)
This study aimed to assess the effectiveness of Capparis Spinose (CS) in preventing the initiation and progression of experimental periodontitis and to evaluate the effect of its on systemic oxidative stress in rats by experimental periodontitis model. Twenty-four male rats were equally divided into; Ligatured (L), non-ligatured (NL), and Ligatured with CS (11 days/day per 20 mg/kg) (LC) groups. Experimental periodontitis was induced with the silk suture technic. Alveolar bone loss was examined, and total antioxidant capacity(TAOC), total oxidant status(TOS), and oxidative stress index(OSI) were analyzed in rat serum. Although; alveolar bone loss showed statistically significant lower values in the LC group compared to L (p < 0.05), not NL. In the LC group, osteoclast and osteoblast numbers were statistically significant compared to L, but there were no statistical differences between LC and NL. Serum TAOC levels were signiﬁcantly lower in group L compared to others and also LC group showed significant differences from NL. TOS and OSI levels were signiﬁcantly higher in group L than in other groups. Within the limitation of the present study, it can be said that the destruction via local inflammation that may occur after the experimental periodontitis can be prevented by using CS.